Theoretical study on near UV and visible optical absorption characteristics of Ti-doped α-Al2O3 single crystals. (September 2021) - Gong, Qiaorui; Zhao, Chengchun; Li, Shanming; Zhao, Geng; Xu, Min; Hang, Yin
Abstract: A first principles method is used to study the origin of the near-ultraviolet (300∼400 nm) and visible absorption band (400∼600 nm) in Ti-doped α-Al2 O3 crystals. The electronic and optical properties of Al2 O3 supercells containing substitutional Ti 3+, interstitial Ti 3+ and various Ti ion pairs were calculated. The results show that the absorption peaks at 388 (reported) and 325 nm (unreported) are both caused by the charge transfer transition from the substitutional Ti 3+ 3d orbital to the adjacent Al 3+ 3s3p orbital. When interstitial Ti 3+ and Al vacancy coexist, the interstitial Ti 3+ will relax to the position of the adjacent Al vacancy, forming a defect like substitutional Ti 3+ . The line-contact Ti 3+ -Ti 3+, face-contact Ti 3+ -Ti 3+ and point-contact Ti 4+ -Ti 3+ ion pairs are the main causes for the multi-peak configuration and small bumps in the visible absorption band. Moreover, two other possible causes for this phenomenon are supplied from the perspective of ligand field theory and thermal activation.